(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The defence of open society has been the main mission of the Central European University (CEU) since its creation in 1991. This article explores the history of the CEU, from the crucial years of the immediate post-Cold War until the present day. It is divided into two parts: the first part analyses the origins of the CEU, its aims and the concept of the open society as an academic mission; the second part focuses on the clash between the CEU and the Hungarian government, led by right-wing populist minister Viktor Orbán. The “CEU affair” has opened a debate about the nature of the relationship between academic freedom, open society and the rule of law in Hungary and in Europe. Reconstructing the history of the CEU offers the chance to explore the evolution of the open society ideal in Central and Eastern Europe, from the euphoria of the post-Cold War to the challenges of the 21st century.